Psychometric indicators and adaptation ch. Osgud’s method "semantic differential" (ukrainian version of the method - Yanovska, S.; Sevostyanov, P.; Turenko, R. (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2023)
The article presents the results of adaptation and standardization of the Semantic Differential method (Ch. Osgood). The purpose of the article was to adapt the Ukrainian version of the Semantic Differential method and determine the possibilities of its use in further psychological research. In order to meaningfully validate the adapted version of the Semantic Differential method, five experts were involved - philological specialists in the field of English-Ukrainian translation. In the course of joint work with experts, the following was carried out: direct translation of the original text of the method of semantic differential by Ch. Osgood; retroversion; correction of the translated material in order to increase the degree of compliance with the linguistic features of Ukrainian speakers (taking into account compliance with the theoretical construct of the methodology); final substantive and linguistic evaluation of the Ukrainian-language version; selection of the optimal sequence of pairs of adjectives. The work was carried out in several stages: translation; expert substantive evaluation of the preliminary translation; standardization of the questionnaire; collection of relevant norms on the domestic sample (563 persons (24.01-11.95 years old), among whom 198 are carriers of the male gender; 365 – female). All subjects were fluent in the Ukrainian language; the level of knowledge of English is not lower than B1 (Intermediate). Language knowledge was tested using express methods on the eve of testing. The testing took place in the following order: the original (English) version of the Semantic Differential (the attitude towards oneself was assessed); Rosenberg self-esteem scale; subjective scaling of one’s self; adapted author’s Ukrainian modification of the Semantic Differential (attitude towards oneself was also assessed). During the analysis of the psychometric indicators of the adapted version of the methodology, its content and construct validity were checked; reliability and coherence of its points; in addition, test norms for the Ukrainian-speaking sample were obtained. Test norms were determined separately for groups of men and women. It was established that the adapted version of the Semantic Differential is characterized by high psychometric indicators, so it allows the use of the method for further study of the attitude to phenomena determined by the purpose of a separate study.